Eco-friendly Super Sulphated Cement Concrete Using Vietnam Phosphogypsum and Sodium Carbonate Na2CO3 - Ngoc Lam Nguyen; Phuong Le Vu (Salehan Institute of Higher Education, 2022)
Sustainable development is one of the critical topics in the construction industry today, especially in reducing CO2 emissions and production energy costs. There have been many studies worldwide on using ground granulated blast furnace slag combined with phosphogypsum (PG) to replace binder (B) in making concrete. However, this topic in Vietnam has not received much attention despite the large backlog of phosphogypsum waste. One of the main disadvantages limiting the feasibility of super-sulphated binders in concrete is the relatively slow hydration and hardening processes, which affect the rate of strength development of mortar and concrete, especially at an early age. In this study, the use of Na2CO3 salt as a quick, solid additive can overcome the disadvantages of this type of binder. Research results show that using 15 to 25% phosphorus gypsum waste (PG) and a combination of 60 to 80% finely granulated blast furnace slag (GGBFS) with a small amount of cement and an activator like Na2CO3can replace cement in making concrete. The concrete mix has good workability, and the maximum compressive strength after 28 days can reach over 50 MPa. Using industrial wastes as the main ingredients to make binders will improve sustainable development, reducing environmental pollution and the cost of mortar and concrete products in construction. Doi: 10.28991/CEJ-2022-08-11-06 Full Text: PDF